Contributions of traditional and HIV-related risk factors on non-AIDS-defining cancer, myocardial infarction, and end-stage liver and renal diseases in adults with HIV in the USA and Canada: a collaboration of cohort studies. Issue 2 (February 2019) - Althoff, Keri N; Gebo, Kelly A; Moore, Richard D; Boyd, Cynthia M; Justice, Amy C; Wong, Cherise; Lucas, Gregory M; Klein, Marina B; Kitahata, Mari M; Crane, Heidi; Silverberg, Michael J; Gill, M John; et al.
Summary: Background: Adults with HIV have an increased burden of non-AIDS-defining cancers, myocardial infarction, end-stage liver disease, and end-stage renal disease. The objective of this study was to estimate the population attributable fractions (PAFs) of preventable or modifiable HIV-related and traditional risk factors for non-AIDS-defining cancers, myocardial infarction, end-stage liver disease, and end-stage renal disease outcomes. Methods: We included participants receiving care in academic and community-based outpatient HIV clinical cohorts in the USA and Canada from Jan 1, 2000, to Dec 31, 2014, who contributed to the North American AIDS Cohort Collaboration on Research and Design and who had validated non-AIDS-defining cancers, myocardial infarction, end-stage liver disease, or end-stage renal disease outcomes. Traditional risk factors were tobacco smoking, hypertension, elevated total cholesterol, type 2 diabetes, renal impairment (stage 4 chronic kidney disease), and hepatitis C virus and hepatitis B virus infections. HIV-related risk factors were low CD4 count (<200 cells per μL), detectable plasma HIV RNA (>400 copies per mL), and history of a clinical AIDS diagnosis. PAFs and 95% CIs were estimated to quantify the proportion of outcomes that could be avoided if the risk factor was prevented. Findings: In each of the study populations for the four outcomes (1405 of 61 500 had non-AIDS-defining cancer, 347 of 29 515 had myocardial infarctions, 387 of 35 044 had end-stage liver disease events, and 255 of 35 620 had end-stage renal disease events), about 17% were older than 50 years at study entry, about 50% were non-white, and about 80% were men. Preventing smoking would avoid 24% (95% CI 13–35) of these cancers and 37% (7–66) of the myocardial infarctions. Preventing elevated total cholesterol and hypertension would avoid the greatest proportion of myocardial infarctions: 44% (30–58) for cholesterol and 42% (28–56) for hypertension. For liver disease, the PAF was greatest for hepatitis C infection (33%; 95% CI 17–48). For renal disease, the PAF was greatest for hypertension (39%; 26–51) followed by elevated total cholesterol (22%; 13–31), detectable HIV RNA (19; 9–31), and low CD4 cell count (13%; 4–21). Interpretation: The substantial proportion of non-AIDS-defining cancers, myocardial infarction, end-stage liver disease, and end-stage renal disease outcomes that could be prevented with interventions on traditional risk factors elevates the importance of screening for these risk factors, improving the effectiveness of prevention (or modification) of these risk factors, and creating sustainable care models to implement such interventions during the decades of life of adults living with HIV who are receiving care. Funding: National Institutes of Health, US Centers for Disease Control and Prevention, the US Agency for Healthcare Research and Quality, the US Health Resources and Services Administration, the Canadian Institutes of Health Research, the Ontario Ministry of Health and Long Term Care, and the Government of Alberta.